Granular Pumice Stone: A Natural Double-Porosity Sound-Absorbing Material - Jorge P. Arenas; Claudio C. Parra; Juan Rebolledo; Rodolfo Venegas (Buildings)
Pumice forms when a volcanic explosion ejects highly pressurized, superheated rock, rapidly cooling and depressurizing, resulting in a porous structure. In countries with high volcanic activity, pumice stone is a low-cost natural material that is lightweight, non-toxic, eco-friendly, durable, and heat-resistant. Among other applications, pumice has been used as an aggregate to produce lightweight concrete or cementitious material to produce blended cement or geopolymer. Since pumice stone is highly porous, it could be used as a naturally occurring multiscale porous sound-absorbing material, which may add interesting properties for absorbing sound energy. Normally, a double-porosity granular material presents higher sound absorption at low frequencies than a solid-grain material with the same mesoscopic characteristics at a reduced weight. This study uses theoretical and experimental approaches to investigate the sound absorption characteristics of granular pumice samples. The tests were conducted on crushed pumice stones in granular form. The study suggests that pumice stones can be used as a novel material for sound absorption in room acoustics and noise control applications.